Oil Pollution of the South-Eastern Baltic Sea and the Gulf of Finland - A. G. Kostianoy; E. V. Bulycheva; O. Yu. Lavrova; M. I. Mityagina (Проблемы постсоветского пространства)
The article summarizes the information about oil pollution in the southeastern part of the Baltic Sea and the Gulf of Finland, obtained on the basis of long-term data of satellite and aircraft observations. It is shown that the main sources of oil pollution of the Baltic Sea are ships of various types. The main areas of oil pollution of the Baltic Sea, which are connected with the main shipping lanes and approaches to the ports of the Baltic countries, are detected.